Influence of roughness, aspect ratio and reynolds number on shea’r stress in channels and non-pressurized closed ducts - Olivero Novillo, María Luisa; Aguirre Pe, Julián (Rev. Téc. Fac. Ing. Univ. Zulia)
With the purpose of obtaining shear stress distributions at the walls and at the bed, of an open channel, experimental data available in literature. for smooth open channels and smooth rectangular ducts, are analyzed and confronted. Similitude criteria between a free surface flow and a close non-pressurized flow are given. The influence of the aspect ratio on shear distribution is determined and different functional relationships are obtained. Mean shear stresses at the walls and at the bed are analyzed and empirical relationships are obtained. Experimental equations show satisfactory correlation coefficients.